The Positive Association Between Duration of Skin-to-Skin Contact and Blood Glucose Level in Full-Term Infants. Issue 4 (October 2018) - Takahashi, Yuki; Tamakoshi, Koji
Abstract : The aim of this study was to evaluate the contribution of the duration of skin-to-skin contact (SSC) on blood glucose levels at 2 hours after birth in healthy full-term infants. This observational study was done at one of the baby-friendly hospitals located in Aichi, Japan in 2009. Sixty newborn infants who were born vaginally from uncomplicated pregnancies were participated. All infants were held SSC within 5 minutes. All data regarding neonatal information, blood glucose levels at 2 hours of age, and maternal information were obtained from their medical history. Multiple linear regression analysis was performed to identify the independent contribution of the duration of SSC. The mean duration of SSC was 59.6 ± 13.6 minutes (range: 11.0-97.0 minutes) and the infant blood glucose level was 53.1 ± 9.5 (range: 30.0-80.0 mg/dL) mg/dL. The duration of SSC (β [95% confidence interval] = .282 [range: 0.037-0.357], standardized β = .282, P < .017) was significantly and positively associated with infant blood glucose levels independent of gestational age, birth weight, sex, length of second-stage labor, and mode of delivery. Thus, the longer early SSC was associated with higher blood glucose level at 2 hours of age in healthy full-term infants.